2016
DOI: 10.1016/j.memsci.2015.09.031
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the transport parameters and physiochemical properties of forward osmosis membranes after treatment of produced water

Abstract: Evaluation of the transport Parameters and physiochemical properties of forward osmosis Membranes after treatment of produced water, Journal of Membrane Science, http://dx. AbstractThe application of semipermeable membranes for dewatering of complex oil and gas wastewaters continues to be a topic of increasing interest. Several studies have explored the fouling propensity and contaminant rejection of osmotically driven membranes during forward osmosis (FO) treatment of produced waters; however, none have inves… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(9 citation statements)
references
References 48 publications
1
7
0
Order By: Relevance
“…Investigation of forward osmosis application ranges from lab-scale experiments (with either synthetic or real water) to full-scale implementation (with real water) and covers many fields, including: seawater desalination to produce drinking water [ 62 , 63 , 64 ], emergency water supply with so-called hydration bags [ 78 ], treatment of wastewater from oil and gas production as well as from mining [ 34 , 79 , 80 , 81 , 82 ], agricultural use for fertigation [ 83 , 84 , 85 ], biological wastewater treatment with osmotic membrane bioreactors [ 37 , 86 , 87 , 88 , 89 ], treatment of anaerobic digester centrate [ 90 , 91 ], microbial fuel cells [ 92 , 93 , 94 , 95 , 96 , 97 , 98 ], removal of trace organic compounds [ 99 , 100 , 101 , 102 , 103 , 104 ]. …”
Section: Forward Osmosis Application—state Of Implementationmentioning
confidence: 99%
See 1 more Smart Citation
“…Investigation of forward osmosis application ranges from lab-scale experiments (with either synthetic or real water) to full-scale implementation (with real water) and covers many fields, including: seawater desalination to produce drinking water [ 62 , 63 , 64 ], emergency water supply with so-called hydration bags [ 78 ], treatment of wastewater from oil and gas production as well as from mining [ 34 , 79 , 80 , 81 , 82 ], agricultural use for fertigation [ 83 , 84 , 85 ], biological wastewater treatment with osmotic membrane bioreactors [ 37 , 86 , 87 , 88 , 89 ], treatment of anaerobic digester centrate [ 90 , 91 ], microbial fuel cells [ 92 , 93 , 94 , 95 , 96 , 97 , 98 ], removal of trace organic compounds [ 99 , 100 , 101 , 102 , 103 , 104 ]. …”
Section: Forward Osmosis Application—state Of Implementationmentioning
confidence: 99%
“…treatment of wastewater from oil and gas production as well as from mining [ 34 , 79 , 80 , 81 , 82 ],…”
Section: Forward Osmosis Application—state Of Implementationmentioning
confidence: 99%
“…In addition, the initial rearrangement of the polymeric matrix of the membrane active skin layer may also contribute to the observed flux decline. It has been reported that the reverse salt flux could increase the ionic strength within the interface between the membrane active layer and the feed solution, reducing the electrostatic repulsion among CTA polymer chains and thereby compacting the membrane active layer [43].…”
Section: Membrane Transport Propertiesmentioning
confidence: 99%
“…The market for forward osmosis is growing rapidly owing to the extraordinary progress being made in the fields of membrane development, draw solution, and process design. , Despite the high number of publications and patents being filed in the niche of FO, there are only a limited number of reports which deals with the overall process, i.e., recovery and the quality of final potable/reusable water, ,, with robust FO membranes developed by HTI, Albany, U.S.A. being utilized in most of the FO research works and pilot plants. ,, Further with the pioneering work by Modern Waters & Oasys Water Inc. in developing the process and technology at commercial scale, FO is now competing with other technologies in both seawater desalination and wastewater treatment …”
Section: Introductionmentioning
confidence: 99%